2023
DOI: 10.1063/5.0181630
|View full text |Cite
|
Sign up to set email alerts
|

Sliding motion of highly deformed droplets on smooth and rough surfaces: Shape oscillation, chaotic breakage, corner shape, and pearling

Yu-Hao Tsao,
Ying-Chih Liao,
Heng-Kwong Tsao

Abstract: The sliding behavior of droplets on smooth and rough surfaces with various surface wettabilities is investigated by many-body dissipative particle dynamics simulations. On a smooth surface, as the driving force (Bo) increases, the droplet shape and velocity (Cac) before breakage can be classified into four distinct regimes: (I) nearly spherical cap with Cac∝Bo; (II) oval shape with negative deviation from the linear relation; (III) elongated shape without a neck, where Cac decreases with increasing Bo; and (IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…17–19 Stick–slip motion and other complex behavior have also been observed in prior computational works involving droplets on inclined substrates with multiple topographical defects. 20,21 Prior experimental and theoretical works have shown that chemical patterning can also induce stick–slip motion of droplets on inclined substrates. 22–25…”
Section: Introductionmentioning
confidence: 99%
“…17–19 Stick–slip motion and other complex behavior have also been observed in prior computational works involving droplets on inclined substrates with multiple topographical defects. 20,21 Prior experimental and theoretical works have shown that chemical patterning can also induce stick–slip motion of droplets on inclined substrates. 22–25…”
Section: Introductionmentioning
confidence: 99%